PENGARUH DUKUNGAN ORGANISASI, BEBAN KERJA DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT UMUM SARAH MEDAN - Hutauruk, Ayu Teresia; Silalahi, Esli; Sahat, Sahat (LP2M Universitas Bina Bangsa, 2025)
This research aims to determine the influence of organizational support, workload and work conflict on employee performance at Sarah Medan General Hospital. In this research, the type of data used is primary data, primary data was collected through distributing questionnaires, the research population was 53 medical employees. The techniques used in this research are validity testing, reliability testing, multiple linear regression analysis, hypothesis testing (F test and t test) and coefficient of determination analysis. Based on the results of multiple linear regression, the equation is Y = 11.135 + 0,421X1 - 0,421X2 - 0,500X3 The variables of organizational support, workload, and work conflict simultaneously have a significant effect on Employee Performance at Sarah Medan General Hospital. While partially it shows that organizational support has a positive and significant effect on employee performance at Sarah Medan General Hospital with a multiple linear regression coefficient value of 0.421 and a significant value of 0.001 <0.05 (smaller than the error tolerance value), workload has a negative and significant effect on employee performance at Sarah Medan General Hospital with a multiple linear regression coefficient value of -0.421 and a significant value of 0.003 <0.05 (smaller than the error tolerance), work conflict has a negative and significant effect on employee performance at Sarah Medan General Hospital with a multiple linear regression coefficient value of -0.500 and a significant value of 0.000 <0.05 (smaller than the error tolerance value)